2015
DOI: 10.1111/zph.12227
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Loading From Canada Geese Faeces in Freshwater: Potential Risks to Human Health Through Recreational Water Exposure

Abstract: Canada geese (Branta canadensis) faeces have been shown to contain pathogenic protozoa and bacteria in numerous studies over the past 15 years. Further, increases in both the Canada geese populations and their ideal habitat requirements in the United States (US) translate to a greater presence of these human pathogens in public areas, such as recreational freshwater beaches. Combining these factors, the potential health risk posed by Canada geese faeces at freshwater beaches presents an emerging public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 62 publications
1
25
1
1
Order By: Relevance
“…[96] Refsum alone and together with co-workers [85,90] proposed that the importance of waterfowl in spreading Salmonella bacteria is limited, except for birds resident in areas highly contaminated by human waste or domestic animal manure. However, Gorham and Lee [5] rather emphasized the uncertainty of assessments of potential risks, especially in relation to Canada geese. There are no studies directly linking outbreaks of salmonellosis in humans, livestock or domestic poultry to the presence of swans and geese or their faeces.…”
Section: Gastrointestinalmentioning
confidence: 99%
See 3 more Smart Citations
“…[96] Refsum alone and together with co-workers [85,90] proposed that the importance of waterfowl in spreading Salmonella bacteria is limited, except for birds resident in areas highly contaminated by human waste or domestic animal manure. However, Gorham and Lee [5] rather emphasized the uncertainty of assessments of potential risks, especially in relation to Canada geese. There are no studies directly linking outbreaks of salmonellosis in humans, livestock or domestic poultry to the presence of swans and geese or their faeces.…”
Section: Gastrointestinalmentioning
confidence: 99%
“…[165,166] Although sometimes stated that such transmission is not well understood or documented, a general advice is nevertheless to minimize direct contact between humans and goose faeces. [166] Furthermore, Abulreesh et al [167] argued that skin contact and accidental ingestion of contaminated water from amenity village ponds harbouring waterfowl should be avoided, and Gorham and Lee [5] concluded that as Canada geese can indeed be an important source of faecal contamination of recreational waters, population control of this species may be considered for public health reasons.…”
Section: Potential Transmission Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In urban and suburban areas, large flocks of waterfowl can generate substantial accumulations of faeces in recreational parks and private lawns (Conover, ; Feare, Sanders, Blasco, & Bishop, ). Waterfowl and other birds have also been found to be a significant source of faecal material in recreational waters (Edge & Hill, ; Gorham & Lee, ; Meyer, Appletoft, Schwemm, Uzoigwe, & Brown, ). In rural areas, waterfowl frequently occupy agricultural fields and surface waters for resting and feeding (Fox, Elmberg, Tombre, & Hessel, ), with possible implications for food safety.…”
Section: Introductionmentioning
confidence: 99%